1

Assignment 5 — Solutions 2/13/04 (revised 2/23/04)
Problem 3.10
(a)

We get to integrate our relations from last time. Joy.

V , -p ê 2 < f < p ê 2
-V , p ê 2 < f < 3 p ê 2
3 pê2
L
1
npz
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡
f ‡ z V Hf, zL sinJ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ N
A0n = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
p L Im Hn p b ê LL -pê2
L
0

V Hf, zL = :

3 pê2
L
2
npz
cos m f
A
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡
f ‡ z V Hf, zL :
> sin J ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ N , m ∫ 0
: mn > = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
sin
m
f
Bmn
p L Im Hn p b ê LL -pê2
L
0

The range of f integration has been shifted to be convenient for V (can be done since it's periodic). For m, n ∫ 0:
L
3 pê2
2V
n p z i pê2
A
y cos m f
>
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ z sinJ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ N jj‡
f - ‡
fzz :
: mn > = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
Bmn
p L Im Hn p b ê LL 0
L k -pê2
{ sin m f
pê2
É
Ä
2V
L
n p z L 1 ÅÅÅ sin m f pê2
sin m f 3 pê2 ÑÑÑÑ
>
>
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ B- ÅÅÅÅÅÅÅÅÅÅ cosJ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ NF ÅÅÅÅÅÅ ÅÅÅ:
Ñ
-:
Å
-cos m f pê2 ÑÑÑÖ
p L Im Hn p b ê LL
np
L
0 m ÅÇ -cos m f -pê2
-2 V
2 sinHm p ê 2L - sinH3 m p ê 2L + sinHm p ê 2L
>
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ @H-1Ln - 1D :
0 + cosH3 m p ê 2L - cosHm p ê 2L
n m p2 Im Hn p b ê LL

2 V @1 - H-1Ln D
4 sinHm p ê 2L
>
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ :
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
0
n m p2 Im Hn p b ê LL

A useful table from the CRC handbook of Standard Mathematical Tables and Formulae (30th edition):

sin n p
cos n p

sin n p ê 2

cos n p ê 2

nœ
0
H-1Ln

n even
0
+1
H-1Lnê2
0

n odd
0
-1

H-1LHn-1Lê2
0

n ê 2 odd n ê 2 even
0
0
+1
+1
0

0

-1

+1

from which we deduce that Amn = 0 for even m and Amn ∂ H-1LHm-1Lê2 for odd m. Am0 = 0 = Bm0 from
sinHn p z ê LL§n=0 = 0 and B0n = 0 since sin m f§m=0 = 0. Also A0n = 0 because the f integral is over V Hf, zL only
which is odd in the given range. Since Amn ∂ 1 - H-1Ln it vanishes for even n, and the factor is 2 for odd n.
Finally:
16 V H-1LHm-1Lê2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ , n, m odd ; all other coefficients vanish
Amn = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
n m p2 Im Hn p b ê LL

2

H-1LHm-1Lê2
16 V
npz
npv
FHv, f, zL = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ „ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ cosHm fL sinJ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ N IJ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ N
p2
n m p2 Im Hn p b ê LL
L
L
n,m odd

(b)

For b ê L ` 1, which means v ê L ` 1 since v § b, we have from the asymptotic expansion 3.102:

Hn p v ê 2 LLm ê H2 m + 2L!
v m
Im Hn p v ê LL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ º ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅ º J ÅÅÅÅÅÅÅÅ N
Im Hn p b ê LL
Hn p b ê 2 LLm ê H2 m + 2L!
b

One might worry that the arguments to Im are not strictly always small since n ranges to infinity, but in a completely handwaving manner one may hope that the effects of increasing n in numerator and denominator magically cancel out. For those of you who are rightly dubious you can probably go to the series expansion (Gradshteyn and Ryzhik 8.445):

1
z n+2 k
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅ J ÅÅÅÅÅ N
(exact)

In HzL =
k
!
GHn
+
k
+
1L
2
k=0

and use the binomial theorem etc. to figure out the specifics. If you manage do please tell. Anyway at z = L ê 2
and seeing from our table that sin Hn p ê 2L§n odd = H-1LHn-1Lê2 :
H-1LHm-1Lê2
v m
16 V
FHv, f, zL º ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ „ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ H-1LHn-1Lê2 cosHm fL J ÅÅÅÅÅÅÅÅ N
n m p2
b
p2
n,m odd

H-1Ln ¶ H-1Lm
16 V
v 2 m+1
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ „ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‚ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ cos@H2 m + 1L fD J ÅÅÅÅÅÅÅÅ N
p2
2 n + 1 m=0 2 m + 1
b

16 V p ¶ H-1Lm 1
v 2 m+1
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ ‚ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ I‰Â H2 m+1L f + ‰- H2 m+1L f M J ÅÅÅÅÅÅÅÅ N
p2 4 m=0 2 m + 1 2
b
n=0

2 V ¶ H-1Lm
v 2 m+1
v 2 m+1
= ÅÅÅÅÅÅÅÅÅÅÅÅ ‚ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ BJ‰Â f ÅÅÅÅÅÅÅÅ N
+ J‰-Â f ÅÅÅÅÅÅÅÅ N
F
p m=0 2 m + 1
b
b

v
v
2V
= ÅÅÅÅÅÅÅÅÅÅÅÅ Btan-1 J‰Â f ÅÅÅÅÅÅÅÅ N + tan-1 J‰- f ÅÅÅÅÅÅÅÅ NF
b
b
p

Looking up the math handbook (do the trig if you like) gives tan-1 z1 ≤ tan-1 z2 = tan-1 @Hz1 ≤ z2 L ê H1 ¡ z1 z2 LD:
i ‰Â f v ê b + ‰- f v ê b yz
2V
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz =
FHv, f, zL º ÅÅÅÅÅÅÅÅÅÅÅÅ tan-1 jjjj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
 f v ê bL H‰- f v ê bL z
p
1
H‰
{
k

2V
i 2 Hv ê bL cos f y
ÅÅÅÅÅÅÅÅÅÅÅÅ tan-1 jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz
p
k 1 - v2 ê b2 {

Exactly as you should have found in 2.13. Note the shorter route to summing the series, those of you who're
interested.

3

Problem 3.11
(a)

The standard way to show orthogonality is to integrate the differential equation, in this case 3.77:

2 Jn HxL
1 Jn HxL i
0 = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + jjjj1 x x
x2
k

1  i 
n2 y
y i
ÅÅÅÅÅÅÅÅÅ zzzz Jn HxL = ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ jjx ÅÅÅÅÅÅÅÅÅ Jn HxLzz + jjjj1 { k
x2 {
x x k x

1  i 
y i
0 = ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ jj r ÅÅÅÅÅÅÅÅÅ Jn Hk rLzz + jjjjk 2 r r k r
{ k

n2 y
ÅÅÅÅÅÅÅÅÅ zzzz Jn Hk rL
r2 {

n2 y
ÅÅÅÅÅÅÅÅÅ zzzz Jn HxL
x2 {

(1)

Act on both sides with the integral operator Ÿ0a r r Jn H rL and integrate stuff by parts:
a
i
y
n2 y
ij 
y
j r ÅÅÅÅÅÅÅÅÅ Jn Hk rLzz Jn H rL + ‡ r jjjj r k 2 - ÅÅÅÅÅÅÅÅÅ zzzz Jn Hk rL Jn H rLzzzz
r {
k r
{
0
k
{
ÄÅ
ÉÑa
a
a
i
Å

Ñ
Jn Hk rL Jn H rL
= ÅÅÅÅ r Jn H rL ÅÅÅÅÅÅÅÅÅ Jn Hk rLÑÑÑÑ - ‡ r r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ‡ r jjjj r k 2 ÅÅÇ
Ñ
r
r
r
0
0
ÖÑ0
k

0 = ‡


r ÅÅÅÅÅÅÅÅÅ
r
0
a

y
n2 y
ÅÅÅÅÅÅÅÅÅ zzzz Jn Hk rL Jn H rLzzzz
r {
{

We're given that the first term vanishes at the lower limit r = 0 (is it just me or is this trivial, because r = 0 at
r = 0??). The other condition says
ƒƒƒ

1
l
Jn Hk rL ƒƒƒ
Jn Hk rL ƒƒƒ
ÅÅÅÅÅÅÅÅÅ ln@Jn Hk rLD§ƒ
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ §ƒ
= - ÅÅÅÅÅ ï r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ §ƒ
= -l Jn Hk aL
ƒƒ r=a
r
r ƒƒ r=a
r ƒƒ r=a
Jn Hk rL
a

Incidentally we see from this that k is restricted to values such that (2) is satisfied, i.e. k a ª ynn such that
a Jn£ Hynn L + l Jn Hynn L = 0. We can arbitrarily start numbering eigenvalues n = 1, 2, ….
a
i
Jn Hk rL Jn H rL
r r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ‡ r jjjj r k 2 r
r
0
0
k

0 = -l Jn H aL Jn Hk rL - ‡

a

0 = -l Jn Hk aL Jn H rL - ‡

a

a
i
Jn H rL Jn Hk rL
r r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ‡ r jjjj r 2 r
r
0
0
k

y
n2 y
ÅÅÅÅÅÅÅÅÅ zzzz Jn Hk rL Jn H rLzzzz
r {
{

y
n2 y
ÅÅÅÅÅÅÅÅÅ zzzz Jn H rL Jn Hk rLzzzz
r {
{

In the last step I've just renamed k ¨ . Subtracting the second line from the first gives what we want:
0 = ‡

0

a

r r Ik 2 - 2 M Jn Hk rL Jn H rL = Ik 2 - 2 M ‡

0

a

r r Jn Hk rL Jn H rL

since it means that unless k 2 = 2 (in which case the right-hand-side is trivially 0) the integral must vanish.
(b)

f
H f 2 L
Now normalization. This time act on (1) with Ÿ0a r r2 Jn Hk rL ê r and use f ÅÅÅÅÅÅÅÅÅ = ÅÅÅÅ1Å ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ :
r

2

r

(2)

4

Jn Hk rL y
i Jn Hk rL  i Jn Hk rL y
r jj r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ jj r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz + Ik 2 r2 - n2 M Jn Hk rL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz
r
r k
r {
r {
k
0
2
2
a
a
a
1
n2
 i Jn Hk rL y
Jn Hk rL

= ÅÅÅÅÅ ‡ r ÅÅÅÅÅÅÅÅÅ jj r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz + k 2 ‡ r r2 Jn Hk rL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅ ‡ r ÅÅÅÅÅÅÅÅÅ @Jn Hk rLD
2 0
r {
r
r k
2 0
r
0

0 = ‡

a

(3)

Integrate the second term by parts:

a
Jn Hk rL

a
r r2 Jn Hk rL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = k 2 Ar2 Jn2 Hk rLE0 - k 2 ‡ r Jn Hk rL ÅÅÅÅÅÅÅÅÅ Ar2 Jn Hk rLE
r
r
0
0

k2 ‡

a

= k 2 a2 Jn2 Hk aL - 2 k 2 ‡

a

r r Jn Hk rL Jn Hk rL

Jn Hk rL
r Jn Hk rL r2 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
r
0

-k 2 ‡

0

a

Move the last term to the left, divide everything by 2, and we get

a
1
Jn Hk rL
r r2 Jn Hk rL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅ k 2 a2 Jn2 Hk aL - k 2 ‡ r r Jn Hk rL Jn Hk rL
r
2
0
0

k2 ‡

a

Getting back to (3), and using (2) to get rid of the derivative in the evaluation of the first term at r = a:
É
Ä
a
1 ÅÅÅÅij Jn Hk rL yz2 ÑÑÑÑa 1 2 2 2
0 = ÅÅÅÅÅ ÅÅÅj r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ z ÑÑÑ + ÅÅÅÅÅ k a Jn Hk rL - k 2 ‡ r r Jn Hk rL Jn Hk rL r { ÑÖ0 2
2 ÅÇk
0
a
l2
1
= ÅÅÅÅÅÅÅÅÅ Jn2 Hk aL + ÅÅÅÅÅ k 2 a2 Jn2 Hk aL - k 2 ‡ r r Jn Hk rL Jn Hk rL 2
2
0

n2
ÅÅÅÅÅÅÅÅÅ AJn2 Hk rLE
2
0

n2
ÅÅÅÅÅÅÅÅÅ Jn2 Hk aL +
2

a

n2
ÅÅÅÅÅÅÅÅÅ Jn2 H0L
2

Note that Jn H0L is not generally 0! For instance J0 H0L = 1 which we can see from the series expansion 3.82.
a2 ij
2 Hk rL = ÅÅÅÅ
r
r
J
ÅÅÅÅÅ jjj1 +

n
2 k
0
a

n2
l2 - n2 y
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz Jn2 Hk aL + ÅÅÅÅÅÅÅÅÅÅÅÅÅ Jn2 H0L
k 2 a2 {
2 k2

Actually it is more useful for later comparison to leave the derivative as is:
n2 y
a2 i
r r Jn2 Hk rL = ÅÅÅÅÅÅÅÅÅ jjjj1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz Jn2 Hk aL +
2 k
k 2 a2 {
0

a

a2
ÅÅÅÅÅÅÅÅÅ
2

n2
ij Jn Hk rL yz2
j ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ z + ÅÅÅÅÅÅÅÅÅÅÅÅÅ Jn2 H0L
2 k2
k r {

In general proving completeness of a set of functions is a lengthy process which I will forego here. Consult a
math handbook if you're interested, for instance chapter 9 of Arfken which deals with Sturm-Liouville theory. In
our case the differential operator in (1) can be put into self-adjoint form by multiplying it by x:
2 Jn HxL
Jn HxL i
x ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + jjjjx 2
x
x
k

n2 y
ÅÅÅÅÅÅÅÅÅ zzzz Jn HxL = 0
x {

5

Now the necessary and sufficient condition for self-adjointness is that p£ HxL = qHxL where pHxL = x is the coefficient of the second-order term and qHxL = 1 the coefficient of the first-order term, which is obviously satisfied. In
Quantum Mechanics terminology a self-adjoint operator is Hermetian, and just as in there their eigenfunctions
form a complete set. With this in mind we can write
ynn r
f HrL = ‚ An Jn J ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ N where a Jn£ Hynn L - l Jn Hynn L = 0
a
n=1

To extract An we do the usual acting on both side with Ÿ0a r r Jn Hynn r ê aL:

a
ynn r
ynn r
ynm r
ÅÅÅÅÅÅÅÅ
Å
ÅÅÅ
Å
ÅÅÅÅ
N
=
r
f
HrL
r
J
J
Am ‡ r r Jn J ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ N Jn J ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ N

n

a
a
a
0
0
m=1

ÄÅ 2
ÅÅ a i
n2 y
= „ Am dmn ÅÅÅÅ ÅÅÅÅÅÅÅÅÅ jjjj1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz Jn2 Hk aL +
ÅÅÇ 2 k
k 2 a2 {
a

Ä
2 ÅÅÅÅij
n2 y
i Jn Hk rL y2
An = ÅÅÅÅÅÅÅÅÅ ÅÅÅjjj1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz Jn2 Hk aL + jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz +
a2 ÅÅÇk
k 2 a2 {
k r {
m=1

a2
ÅÅÅÅÅÅÅÅÅ
2

É
n2 2 ÑÑÑÑ
ij Jn Hk rL yz2
j ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ z + ÅÅÅÅÅÅÅÅÅÅÅÅÅ Jn H0LÑÑÑ
ÑÑÖ
2 k2
k r {

É-1 a
n2 a2 2 ÑÑÑÑ
ynn r
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ Jn H0LÑÑÑ ‡ r f HrL r Jn J ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ N
ÑÑÖ
a
4 k2
0

If you find out what Jackson did with the Jn2 H0L term please let me know.

Problem 3.12
(a)
In cylindrical coordinates we can expand F as in 3.106 (remember that we want finiteness for all of
z ¥ 0). Since we have azimuthal symmetry it must be that there is no f dependence, i.e. all the Am 's and Bm 's
vanish except for B0 ª AHkL:
FHv, f, zL = ‡

0

k AHkL ‰-k z J0 Hk vL

Using the orthogonality condition 3.108 and the z = 0 boundary condition F§z=0 = V QHv - aL, act on both sides
with Ÿ0¶ v v J0 H vL at z = 0:

0

v FHv, f, zL v J0 H vL = ‡
V‡

0

0

a

v v J0 H vL = ‡

k AHkL ‡

0

v v J0 Hk vL J0 H vL

1
1
k AHkL ÅÅÅÅÅ dH - kL = ÅÅÅÅÅ AHL
k

0

AHkL = k V ‡

0

a

v v J0 Hk vL

From Gradshteyn and Ryzhik 5.52 (W is any of N , H H1L or H H2L ):

6
n+1 W HxL = xn+1 W
n
‡ x x
n+1 HxL

Changing integration variables for AHkL to x ª k v, so x ª k v:
ka
ka
V
V
AHkL = ÅÅÅÅÅÅ ‡
x x J0 HxL = ÅÅÅÅÅÅ x J1 HxL
= a V J1 Hk aL
k 0
k
0

FHv, f, zL = a V ‡

0

k J1 Hk aL ‰-k z J0 Hk vL

(b)
Perpendicular above the center of the disk means v = 0. Using J0 H0L = 1and Gradshteyn and Ryzhik
6.611:

0

x ‰-a x Jn Hb xL =

FH0, f, zL = a V ‡

0

è!!!!!!!!!!!!!!!!
n
b-n I a2 + b2 - aM
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
è!!!!!!!!
!!!!!!!! ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ , Re n > -1 and ReHa ≤ Â bL > 0
a2 + b2

è!!!!!!!!
!!!!!!!
z2 + a2 - z
-k
z
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅ!ÅÅÅÅÅÅ
k J1 Hk aL ‰
= a V ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
è!!!!!!!!
!!!!!!
a z 2 + a2

z
i
y
= V jjj 1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
ÅÅÅÅ!ÅÅ zzz
è!!!!!!!!
!
!!!!!
a2 + z2 {
k

(c)
Above the edge is at v = a. Setting n = 0 in 3.87, we find that W-1 = W+1 [as an aside: W-n = H-1Ln Wn
holds for arbitrary n œ ]. Setting n = 0 in 3.88, we find 2 W£0 = W-1 - W+1 = -2 W1 . Thus J1 HxL = -J0 HxL ê x:

k J0 Hk aL ‰-k z ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ J0 Hk aL
Hk aL
0
0




= -V A‰-k z J02 Hk aLE0 + a V ‡ k J02 Hk aL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‰-k z + a V ‡ k J0£ Hk aL ‰-k z J0 Hk aL
Hk aL
0
0

FHa, f, zL = a V ‡

k J1 Hk aL ‰-k z J0 Hk aL = -a V ‡

From 3.91 we know that J0 Hk aL remains finite as k Ø ¶, so the upper limit of the first term is just 0. Also we
move the last term to the other side and get
-2 a V ‡

0

k J0£ Hk aL ‰-k z J0 Hk aL = V J02 H0L + a V ‡

Recall that J0 H0L = 1. From Gradshteyn and Ryzhik 6.612:

z
k J02 Hk aL ÅÅÅÅÅ ‰-k z
a
0

yz
ij
2
2b
x ‰-a x J02 Hb xL = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
ÅÅ K jjj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅ
Å zzz
è!!!!!!!!
!
!!!!!!!
!
!!
è!!!!!!!!
!
!!!!!!!
!
!!
0
p a2 + 4 b2 k a2 + 4 b2 {
V
Vz
2
2a
y
i
FHa, f, zL = ÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅ!ÅÅÅ! Å K jjj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ!Å!ÅÅÅ zzz
è!!!!!!!!
!
!!!!!!!
è!!!!!!!!
!
!!!!!!!
2
2 p z2 + 4 a2 k z2 + 4 a2 {

V
FHa, f, zL = ÅÅÅÅÅÅ
2

zk
2a
ij
y
ÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ!Å!ÅÅÅ
j1 + ÅÅÅÅÅÅÅÅÅÅ KHkLzz , k ª ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
è!!!!!!!!
!!!!!!!!
pa
k
{
z2 + 4 a2

Master your semester with Scribd & The New York Times

Special offer for students: Only $4.99/month.

Master your semester with Scribd & The New York Times

Cancel anytime.